Ventricular Tachycardia or Fibrillation Storm in Coronavirus Disease. (18th August 2022) - Khan, Muhammad H.; Aqtash, Obadah; Harris, David M.; Costea, Alexandru I.; Gerson, Myron C.
Abstract : Ventricular tachycardia (VT) or ventricular fibrillation (VF) storm associated with severe acute respiratory syndrome coronavirus 2 infection is a potentially fatal complication; the correlation of these 2 disorders, however, has not been well studied. This retrospective case series examined outcomes of 2 patients who were admitted for repeated implantable cardioverter-defibrillator shocks with or without syncope and observed to have VT/VF storms with COVID-19. Mechanisms of VT/VF storms in COVID-19 are multifactorial including myocarditis, systemic inflammation, hyperadrenergic state, hemodynamic instability, hypoxia, acidosis, and proarrhythmic drugs. A higher incidence of VT/VF storm is observed in patients with comorbidities and those requiring critical care, with some studies reporting increased mortality. In our cohort, 1 of the 2 patients succumbed to the complications from COVID-19, and the other patient was discharged to home in stable condition. Monitoring of life-threatening arrhythmias in the setting of COVID-19 may need to be adopted to prevent morbidity and mortality.